Gain-scheduled H-infinity control for tensor product type polytopic plants - Chumalee, Sunan; Whidborne, James F. (Wiley, 2014)
A tensor product (TP) model transformation is a recently proposed technique for transforming a given linear parameter-varying (LPV) model into polytopic model form, for which there are many methods that can be used for controller design. This paper proposes an alternative approach to the design of a gain-scheduled output feedback H∞ controller with guaranteed L2-gain parameter-dependent performance for a class of TP type polytopic models using parameter-dependent Lyapunov functions where the linear matrix inequalities (LMIs) need only to be evaluated at all vertices of the system state-space model matrices and the variation rate of the scheduled parameters. In addition, a construction technique of the intermediate controller variables is also proposed as a matrix-valued function in the polytopic coordinates of the scheduled parameters. The performance of the proposed approach is tested on a missile autopilot design problem. Furthermore, nonlinear simulation results show the effectiveness of these proposed techniques.
Keywords: Tensor product model system; Linear parameter-varying system; Gain-scheduling control; Nonlinear control; Parameter-dependent Lyapunov functions; Linear matrix inequality